PERAN ORANG TUA DALAM MENINGKATKAN KEDISIPLINAN ANAK USAI 5-6 TAHUN DI TK AL-ADABIY PONTIANAK - Ewita Putri Suhirman; Marmawi R; Desni Yuniarni (Universitas Tanjungpura, 2021)
AbstractThis study aims to determine the role of parents in improving the discipline of children aged 5-6 years at Tk Al-Adabiy Pontianak. The method used in the study This is a descriptive method with a qualitative research form. The subjects in the study were parents and children aged 5-6 years at TK AlAdabiy Pontianak. The data collection techniques used in the study were observation, interviews and documentation. The results showed that: 1. The role of parents in providing self-examples to improve children's discipline, parents always give a warning if they make a mistake. 2. The role of parents in creating togetherness with children to realize moral values in creating children's discipline, namely teaching children to always say greetings, and always respect their elders and fellow friends. 3. The role of parents in living the world of children to create child discipline, namely parents respond and understand children. 4. The role of parents in providing logical consequences to improve children's discipline, namely parents provide consequences that are mutually agreed upon. 5. The role of parents in controlling children's behavior to improve children's discipline is that parents always control children's behavior. Thus the role that has been implemented by parents to improve discipline for children aged 5-6 years at Tk Al-Adabiy Pontianak has been carried out well.Keywords: Role of Teachers, Independence of Children